2007
DOI: 10.1186/1471-2148-7-115
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of interaction specificity of fungus-growing termites and Termitomyces symbionts in South Africa

Abstract: Background: Termites of the subfamily Macrotermitinae live in a mutualistic symbiosis with basidiomycete fungi of the genus Termitomyces. Here, we explored interaction specificity in fungus-growing termites using samples from 101 colonies in South-Africa and Senegal, belonging to eight species divided over three genera. Knowledge of interaction specificity is important to test the hypothesis that inhabitants (symbionts) are taxonomically less diverse than 'exhabitants' (hosts) and to test the hypothesis that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
84
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(91 citation statements)
references
References 37 publications
7
84
0
Order By: Relevance
“…Moreover, the degree of co-speciation between the two partners is very low. These findings confirm earlier results showing that specificity exists mainly at the generic level but not within genera (Aanen et al 2002(Aanen et al , 2007. Termitomyces symbionts associated with Malagasy Microtermes belong to three different clades and have in general identical or very similar haplotypes to known continental African symbionts (figure 2): (I) a large well-supported cluster containing the majority of the Madagascar haplotypes belonged to a clade together with three South African samples; (II) the only exclusively Madagascar clade is closely related to South African haplotypes; and, finally, (III) a single Madagascar haplotype is very similar to South African representatives.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…Moreover, the degree of co-speciation between the two partners is very low. These findings confirm earlier results showing that specificity exists mainly at the generic level but not within genera (Aanen et al 2002(Aanen et al , 2007. Termitomyces symbionts associated with Malagasy Microtermes belong to three different clades and have in general identical or very similar haplotypes to known continental African symbionts (figure 2): (I) a large well-supported cluster containing the majority of the Madagascar haplotypes belonged to a clade together with three South African samples; (II) the only exclusively Madagascar clade is closely related to South African haplotypes; and, finally, (III) a single Madagascar haplotype is very similar to South African representatives.…”
Section: Resultssupporting
confidence: 92%
“…Even though all of the five species of Microtermes studied so far have vertical transmission, earlier studies (Aanen et al 2002(Aanen et al , 2007 have indicated that occasional events of horizontal transmission also occur in the genus Microtermes. Such occasional horizontal transmission must explain the present result that multiple non-sister lineages of Termitomyces are associated with the fungus-growing termites of Madagascar.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…Within a colony, crop mixing does not occur as the fungal symbionts are always reared as single-strain monocultures regardless of the symbiont transmission mode. 2,[15][16][17][18] It has recently been shown that single-strain monocultures of Termitomyces within single nests are maintained through positive frequency-dependent selection. 15 This mechanism thus prevents subsequent occupation of the comb by other fungal strains.…”
Section: Dispersion and Colonization By Fungus-growing Termitesmentioning
confidence: 99%
“…Considering the symbionts' point of view, selection favors dispersal out of the host addition, the gathering of Termitomyces spores by fungus-growing termites seems to be a selective process, as suggested by the observed patterns of co-evolution. 2,16,22 It remains to be tested how this selectivity occurs.…”
Section: Dispersion and Colonization By Fungus-growing Termitesmentioning
confidence: 99%